EXPERIMENTAL TESTING OF THE MODIFIED METHOD OF INTRAVITREAL INJECTION IN THE RABBIT EYE - A. V. Kalatanova; A. E. Katelnikova; M. N. Makarova; V. G. Makarov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes theoretical foundations and successful experimental testing of a modified method of intravitreal injection (IVI) in the rabbit eye performed in the laboratory. The method needed modification because preoperative preparation described in available guidelines on IVI requires the use of medicines that are not suitable for use in vivariums in the Russian Federation. The IVI procedure for rabbits was modified by using an anesthetic regime reproducible in Russia and available eye preparations. The anesthetics used were Zoletil 50® («Virbac», France) At a dose of 1.1 mg/kg and Rometar («Bioveta, a.s.», Czech Republic) At a single intravenous dose of 5.6 mg/kg. additional analgesia was achieved by a single intramuscular injection of Ketonal® («Lek d.d.», Slovenia) At a dose of 5 mg/kg. The local anesthetic used was Inokain® eye drops («Promed Exports Pvt. Ltd.», India), the antiseptic used was Betadine® (JSC «EGIS Pharmaceutical plant», Hungary) diluted with water in the proportion of 1:10. The results of clinical examination of animals following IVI performed by lab researchers during unassisted skill training were analysed, and the results of assessment of adverse reactions associated with IVI were expressed as scores and reflected in primary records. The suggested method demonstrated good reproducibility and, therefore, may be recommended for use in preclinical studies of ophthalmic drug products in Russia.